Analysis of the essential oil components from different Carum copticum L. samples from Iran - Zarshenas, Mohammad M. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: The family Apiaceae is defined with the diversity of essential oil. Fruits of Ajwain (Carum copticum), a famous herb of Apiaceae, accumulate up to 5% essential oil which is remarked as important natural product for food and flavoring industry, as well as pharmacological approaches. It is believed that differences in essential oil profile in a certain plant are resulted from various cultivation situations and locations, time of cultivation and also different extracting method. OBJECTIVE: Present study aimed to evaluate major components of ten different collected Ajwain samples from random cultivation locations of Iran. MATERIALS AND METHODS: Samples were individually subjected to hydrodistillation using a Clevenger-type apparatus for the extraction of essential oil. GC/MS analysis for samples was carried out using Agilent technologies model 7890A gas chromatograph with a mass detector. RESULTS: The yield of extracted essential oil was calculated as 2.2 to 4.8% (v/w) for ten samples. Major oil components were thymol, para-cymene and gamma-terpinene. Five of ten samples have thymol as the main component with amount of 35.04 to 63.31%. On the other hand, for four samples, para-cymene was major with amount of 40.20 to 57.31% and one sample had gamma-terpinene as main constituent containing 37.43% of total oil. Accordingly, three different chemotypes, thymol, para-cymene and gamma-terpinene can be speculated from collected samples. CONCLUSION: While these components possess pharmacological effect, screening of different chemotypes not only represent the effect of cultivation situations and locations but also can be beneficial in further investigation.